Zinc Finger-Homeodomain Genes: Evolution, Functional Differentiation, and Expression Profiling Under Flowering-Related Treatments and Abiotic Stresses in Plants. (September 2019) - Shalmani, Abdullah; Muhammad, Izhar; Sharif, Rahat; Zhao, CaiPing; Ullah, Uzair; Zhang, Dong; Jing, Xiu-Qing; Amin, Bakht; Jia, Peng; Mobeen Tahir, Muhammad; Xu, Ze; Chen, Kun-Ming; et al.
Zinc finger-homeodomain (ZHD) proteins constitute a plant-specific transcription factor family that play important roles in plant growth, development, and stress responses. In this study, we investigated a total of 10, 17, and 31 ZHD gene members in the peach, Arabidopsis, and apple genome, respectively. The phylogenetic tree divided the identified ZHD genes into 4 subfamilies based on their domain organization, gene structure, and motif distribution with minor variations. The ZHD gene family members were unevenly distributed throughout in apple, peach, and Arabidopsis genomes. Segmental duplication was observed for 14 pairs of genes in apple. Transcript analysis found that ZHD genes mostly expressed in various tissues, particularly in leaves and flowers. Moreover, the transcript of most ZHD genes was significantly affected at different time points in response to various flowering-related exogenous hormones (sugar, gibberellin [GA], and 6-benzylaminopurine [6-BA]), signifying their possible role in the flowering induction in apple. Furthermore, the transcripts of CaZHD6, CaZHD7, CaZHD3, and CaZHD8 have induced in response to abiotic stresses including heat, drought, salt, and cold, indicating their possible involvement in response to abiotic stresses. Our research work systemically presents the different roles of ZHD genes. We believe that this study will provide a platform for future functional characterization of ZHD genes and to deeply unfold their roles in the regulation of flowering induction in plants.